The sharp solution : a brain-based approach for optimal performance - Hanna, Heidi, 1974- (Wiley, 2013)
Train Your Brain to Energize Your Life In The Sharp Solution, Heidi Hanna introduces readers to a brain-based approach to realistic, sustainable energy management that supports a healthier brain, and as a result a healthier, happier body. By engaging our brain, we can strategically re-wire how we operate, creating more energy and improving productivity while simultaneously reducing stress. As a result, we become more focused and productive, flexible and resilient, and able to sustain higher levels of health and performance over time. These critical aspects of ""cognitive fitnes.